Factores asociados a complicaciones post quirúrgicas de hernia inguinal en el Hospital Isidro Ayora - Pineda Gaona, Nataly Yazmin (2023)
The general rate of complications after inguinal hernia repair is 5-10% and because they are not completely avoidable, it is important to know the associated factors to somehow reduce their incidence. The general objective of the study was to determine the importance of the factors associated with post-surgical complications of inguinal hernia, its specific objectives were to identify the risk factors for post-surgical complications, establish the prevalence of complications and determine the positive and negative predictive value. of the factors associated with post-surgical complications of inguinal hernia at the Isidro Ayora Hospital, period 2020-2021. This research used the qualitative cross-sectional, descriptive approach, the population was made up of 76 patients > 18 years of age operated on at the Isidro Ayora Hospital in Loja, from January 2020 to December 2021, the sample was made up of For 8 patients who presented postsurgical complications, the information collected was processed in the Excel program, in addition the statistical formula of the positive predictive value was used: PV/(FP+PV) and negative predictive value: NV/(FN+VN). It was concluded that the risk factors in which the highest frequency of post-surgical complications were identified were the group > 60 years, male sex, BMI > 25 kg/m2 and in patients with diabetes. The postsurgical complications that occurred most frequently were seroma, surgical wound infection and urinary retention, data that are related to what was mentioned in the literature. The PPV in the group over 60 years of age, male sex, BMI > 25kg/m2 and in patients with comorbidities, resulted in a low probability of presenting complications, a fact that is consistent with the prevalence since both parameters are equivalent, that is, if the prevalence is low the PPV will also be low. The NPV in the group under 60 years of age, female, BMI <25kg/m2, and patients without comorbidity reported a high probability of not presenting complications, a fact that differs from the prevalence since the NPV is inversely proportional to it. That is to say, having a low prevalence, this value tends to increase, because it is useful to rule out complications